CELIAC DISEASE AN UPDATED COMPREHENSIVE REVIEW (International journal of medical sciences, 2025)
Celiac disease CD is a chronic autoimmune disorder of the small intestine triggered by dietary gluten in genetically predisposed individuals Advances in understanding its genetic basis immune mechanisms diagnostic tools and management strategies have markedly improved clinical outcomes This paraphrased review highlights contemporary insights into epidemiology pathogenesis diagnostic approaches clinical variants complications and novel therapeutic perspectives